CSR and its Alignment with uses in 21st Century with Technology Advancement and Betterment (London Journal of Research In Management & Business, 2025)
Thanks to new technologies and rising consumer interest in environmentally responsible company operations, the concept of corporate social responsibility (CSR) has changed dramatically in the modern era. Incorporating digital innovation to improve social and environmental conditions, CSR has evolved from an emphasis on charity and compliance into a strategic undertaking. In order to make their CSR programs more open, efficient, and effective, companies are using new technologies like blockchain, cloud computing, renewable energy, and artificial intelligence (AI). By looking at four market leadersMicrosoft, Google, IBM, and Teslathis study investigates how CSR relates to technical progress. Google is committed to carbon neutrality via the use of data centres powered by renewable energy, while Microsoft employs AI to promote social and environmental sustainability on a global scale. To improve openness and accountability in the supply chain and guarantee ethical conduct, IBM employs blockchain technology. With its groundbreaking electric cars and battery breakthroughs, sustainable energy pioneer Tesla has transformed clean transportation and energy storage solutions. The results show that CSR powered by technology improves company image, encourages entrepreneurship, and creates new market opportunities. In addition to helping with global issues like climate change, digital inclusion, and ethical sourcing, businesses who use technology with an emphasis on corporate social responsibility (CSR) have an advantage in the marketplace. Nevertheless, in order to guarantee good CSR operations, issues including cybersecurity dangers, ethical problems with AI automation, and legal impediments need to be addressed.
Keywords: Chinese corporate tax system; Foreign investment; Export of Chinese products; sustainability; technology; 21st-century; innovation; CSR